Strategi Penyaluran Dan Promosi Pada Produk Pupuk Urea Subsidi Dan Non Subsidi Oleh PT. Pupuk Sriwidjaja - Aunul Azim Riyan Hidayat; Asmai Ishak (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
PT Pupuk Sriwidjaja-Persero (Pusri) is a state-owned enterprise (BUMN) with the sole shareholder being the government of the Republic of Indonesia. PT Pupuk Sriwidjaja is a company that was founded as a pioneer producer of urea fertilizer in Indonesia on December 24 1959 in Palembang, South Sumatra. Pusri started business operations with the main aim of implementing and supporting government policies and programs in the economic and national development sectors, especially in the fertilizer and other chemical industries. This research aims to determine the distribution and promotion strategy for subsidized and non-subsidized urea fertilizer products by Pt. Sriwidjaja Fertilizer. The methodology used in this research uses a qualitative approach, using several data in the form of documents, schemes, information which will later be involved directly and interpreted into further data related to the description of the object to be studied. Through interviews and observations it can be seen that the marketing strategy carried out by PT. Pupuk Sriwidjaja in subsidized and non-subsidized urea fertilizer products using Segmenting, Targeting, Positioning (STP) and also the 7P Marketing Mix Strategy (Product, Promotion, Price, Place, People, Process, Physical Evidence)